2006
DOI: 10.1088/0022-3727/39/24/038
|View full text |Cite
|
Sign up to set email alerts
|

Microchannel flow control through a combined electromagnetohydrodynamic transport

Abstract: A mathematical model is developed to study the combined influences of electromagnetohydrodynamic forces in controlling the fluid flow through parallel plate rectangular microchannels. The electric double layer (EDL) effects are modelled by employing the classical Poisson–Boltzmann equation. The governing fluid flow equations are subsequently solved, in an effort to obtain closed form expressions depicting the variations in the overall flow rate as a function of various influencing system parameters. It is reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 124 publications
(77 citation statements)
references
References 9 publications
2
75
0
Order By: Relevance
“…Certain critical features of electrokinetics [33][34][35][36][37][38][39][40][41] and contact angle characteristics [42] are considered. Closed-form expressions are derived for the various driving and retarding forces, in accordance with a power-law constitutive model.…”
Section: Discussionmentioning
confidence: 99%
“…Certain critical features of electrokinetics [33][34][35][36][37][38][39][40][41] and contact angle characteristics [42] are considered. Closed-form expressions are derived for the various driving and retarding forces, in accordance with a power-law constitutive model.…”
Section: Discussionmentioning
confidence: 99%
“…They simulated the electric double layer (EDL) effects using the classical Poisson-Boltzmann equation, and found that volumetric flow rates are significantly increased with comparatively weak magnetic field, whereas with stronger magnetic fields, significant volumetric forces can oppose and inhibit flow rate augmentation. Other studies include Dey et al [28] who examined heat transfer in electro-osmotic and pressure-driven flows in narrow confinements with thick electric double layers [28]. Mohammadi et al [29] reported very recently on hydrodynamic and direct-current insulator-based dielectrophoresis (H-DC-iDEP) microfluidic blood plasma separation.…”
Section: Introductionmentioning
confidence: 99%
“…A limiting condition can eventually be reached at some threshold value of the magnetic field strength beyond which an increase in the magnitude of the magnetic field strength may even cause the net electromagnetic Lorentz force to become opposing in nature because of a stronger influence of the opposing force over the aiding one. In that case the flow can be completely reversed through the microdevice (Chakraborty and Paul 2006) (refer to Fig. 4).…”
Section: Flow and Thermal Characteristicsmentioning
confidence: 99%